The Study of Enumeration of Live Cells of Microalgae Growth by Using Different Fertilizer Compositions - MOHD ANUAR, NUR ATHIRAH; Norshuhaila Mohamed Sunar (Progress in Engineering Application and Technology, 2025)
This study investigates the growth performance of Botryococcus sp., a promising microalga for biofuel production, under different nitrogen, phosphorus, and potassium (NPK) fertilizer compositions. The microalgae were cultured with three types of fertilizers, namely NPK Blue (16:16:16), NPK Pink (13:13:21), and NPK White (15:15:15), over a period of 28 days. All-important parameters, like cell density, growth phases, and metabolic activity, were monitored to study the different nutrient compositions that affect growth dynamics in Botryococcus sp. The results indicated that NPK White (15:15:15) elicited the quickest and strongest growth, where cell density was highest and active colony formation was observed from Day 26. Due to the balanced nutrient supply, there was sustained energy and metabolic support, thus making it ideal for promoting fast and steady growth. On the other hand, NPK Blue (16:16:16) showed a regular pattern of growth, marked by consistent proliferation of cells with structural integrity. This fertilizer proved suitable for long-term cultivation, offering a stable nutrient supply that avoided rapid depletion. In contrast, NPK Pink (13:13:21) stimulated strong early growth due to its higher potassium content but showed a decline in later stages, probably because of nutrient depletion or imbalance, showing the importance of a balanced nutrient composition. A balanced composition of NPK can give optimal growth and biomass production, obtained in this study.